A Conceptual Framework for Understanding and Reducing Overuse by Primary Care Providers. (October 2013) - Powell, Adam A.; Bloomfield, Hanna E.; Burgess, Diana J.; Wilt, Timothy J.; Partin, Melissa R.
Primary care providers frequently recommend, administer, or prescribe health care services that are unlikely to benefit their patients. Yet little is known about how to reduce provider overuse behavior. In the absence of a theoretically grounded causal framework, it is difficult to predict the contexts under which different types of interventions to reduce provider overuse will succeed and under which they will fail. In this article, we present a framework based on the theory of planned behavior that is designed to guide overuse research and intervention development. We describe categories of primary care provider beliefs that lead to the formation of intentions to assess the appropriateness of services, and propose factors that may affect whether the presence of assessment intentions results in an appropriate recommendation. Interventions that have been commonly used to address provider overuse behavior are reviewed within the context of the framework.